Analisis Wacana Pemberitaan Tentang Konflik Palestina dan Israel Pada Media Online CNBC Indonesia.Com - Reza Ulda Nadila; Achmad Syarifudin; Lilis Sukmawati (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Discourse Analysis of Reporting on the Palestinian and Israeli Conflict on the Online Media CNBC Indonesia.com". News discourse analysis is an approach used to examine and understand the context, structure and meaning implications of text or discourse related to a topic. The problem in this research is how to analyze news discourse about the conflict between Palestine and Israel. This research aims to examine the analysis of news discourse about the conflict between Palestine and Israel. This research uses a qualitative descriptive approach with Teun A.Van Dijk's discourse analysis which is discussed only on the text dimension. This is focused because the object studied is news text. Through observation and documentation carried out by researchers. The results show that the conflict in the news is increasingly continuing due to various factors (1) Attacks and retaliation create a cycle of violence that is difficult to stop, (2) Provocation and response are triggers from both parties, (3) Political disagreements, differences of opinion make it difficult to reach an agreement peace, (4) Casualties and damage to infrastructure further worsen the situation, (5) The presence of extremism from both sides increasingly complicates and prolongs the conflict. Researchers concluded that news about the Palestinian and Israeli conflict on CNBC Indonesia.com was neutral and highlighted the cycle of violence without taking sides. This conflict is difficult to stop because the response to provocation reflects the high tension between the two.